Multimorbidity transitions and the associated healthcare cost among the Finnish adult population during a two-year follow-up - Katja Wikström; Miika Linna; Eeva Reissell; Tiina Laatikainen (Journal of Multimorbidity and Comorbidity)
Background Ageing of the population increases the prevalence and coexistence of many chronic diseases; a condition called multimorbidity. In Finland, information on the significance of multimorbidity and its relation to the sustainability of healthcare is scarce. Aim To assess the prevalence of multimorbidity, the transitions between patient groups with and without multiple diseases and the associated healthcare cost in Finland in 2017–2019. Methods A register-based cohort study covering all adults ( n = 3,326,467) who used Finnish primary or specialised healthcare services in 2017. At baseline, patients were classified as ‘non-multimorbid’, ‘multimorbid’ or ‘multimorbid at risk’ based on the recordings of a diagnosis of interest. The costs were calculated using the care-related patient grouping and national standard rates. Transition plots were drawn to observe the transition of patients and costs between groups during the two-year follow-up. Results At baseline, 62% of patients were non-multimorbid, 23% multimorbid and 15% multimorbid at risk. In two years, the proportion of multimorbid patients increased, especially those at risk. Within the multimorbid at-risk group, total healthcare costs were greatest (€5,027 million), accounting for 62% of the total healthcare cost of the overall patient cohort in 2019. Musculoskeletal diseases, cardiometabolic diseases and tumours were the most common and expensive chronic diseases contributing to the onset of multimorbidity. Conclusion Multimorbidity is causing a heavy burden on Finnish healthcare. The estimates of its effect on healthcare usage and costs should be used to guide healthcare planning.